2002
DOI: 10.1176/appi.neuropsych.14.2.130
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Psychotic Disorder Due to Traumatic Brain Injury: An Analysis of Case Studies in the Literature

Abstract: The authors analyzed data from 69 published case studies of Psychotic Disorder Due to Traumatic Brain Injury (PDTBI) in order to describe its common characteristics and assist in its diagnosis and differentiation from schizophrenia. The majority of these PDTBI patients were males with onset of symptoms occurring within the first 2 years after moderate to severe head injury. A majority showed abnormalities on MRI/CT and EEG with localization in the frontal and temporal areas. The general presentation included d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
85
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(95 citation statements)
references
References 0 publications
8
85
1
1
Order By: Relevance
“…The cranial MRI of our patient showed bilateral frontal severe encephalomacia. It has also been reported that rate of neuroimaging abnormalities was considerably high (65%) in post-traumatic psychosis [2] and frontal-temporal lobes were the most common areas affected in this patient group [1]. Another clue for the diagnosis of post-traumatic psychosis is accompanying cognitive impairment [2] which was prominent in executive functions in our patient.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The cranial MRI of our patient showed bilateral frontal severe encephalomacia. It has also been reported that rate of neuroimaging abnormalities was considerably high (65%) in post-traumatic psychosis [2] and frontal-temporal lobes were the most common areas affected in this patient group [1]. Another clue for the diagnosis of post-traumatic psychosis is accompanying cognitive impairment [2] which was prominent in executive functions in our patient.…”
Section: Discussionsupporting
confidence: 55%
“…It has also been reported that rate of neuroimaging abnormalities was considerably high (65%) in post-traumatic psychosis [2] and frontal-temporal lobes were the most common areas affected in this patient group [1]. Another clue for the diagnosis of post-traumatic psychosis is accompanying cognitive impairment [2] which was prominent in executive functions in our patient. Nonetheless, the presence of other clinical signs of disturbed executive functions and emotional and motivational alterations might rather be attributed to frontal-subcortical system dysfunction and related syndromes (dorsolateral syndrome, orbitofrontal syndrome, and anterior cingulate syndrome), other than solely the process of psychosis.…”
Section: Discussionsupporting
confidence: 55%
“…Van Reekum and colleagues (2000) reviewed data from more recent studies and found a prevalence of post-traumatic schizophrenia of 0.7%. Men appear to be more frequently affected by post-head injury psychosis than women (Fujii et al 2002). David and Prince (2005) appraised the literature to identify a causal role of TBI in schizophrenia and concluded that the evidence for such an association does not exist.…”
Section: Treatmentmentioning
confidence: 99%
“…Prodromal symptoms are common and they include depression, antisocial and inappropriate social behaviour, social withdrawal and deterioration at work. Negative and catatonic features are unusual (Sachdev et al 2001;Fujii & Ahmed, 2002). Sachdev and colleagues (2001) reported a mean latency of 54.7 months between head injury and onset of psychosis, with the minimum being two weeks and the maximum 17 years.…”
Section: Clinical Presentationmentioning
confidence: 99%
See 1 more Smart Citation